DIVERSIFIKASI OLAHAN HASIL PERIKANAN BERBASIS SURIMI KEPADA WADAH PELAYANAN PEREMPUAN DI JEMAAT GPM LEAHARI - Kaya, Adrianus O. W.; Apituley, Margaretha M. A. (Pattimura University, 2025)
Surimi can be processed into a variety of products through diversification of fishery-based processed goods, including meatballs and nuggets. Meatballs and nuggets are derivative products of surimi that are easy to prepare but can yield nutritious products and increase household income through surimi-based processing businesses. Leahari is a coastal village located on Ambon Island with potential in fishery products, particularly fish, but this potential has not been fully utilized, especially in efforts to improve household economic conditions. This community service activity is expected to be a solution for utilizing fish catches to produce nutritious and economically valuable products.